2021
DOI: 10.1055/a-1300-1085
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy versus endoscopic sleeve gastroplasty: a systematic review and meta-analysis

Abstract: Background and study aims Laparoscopic sleeve gastrectomy (LSG) is the current standard for bariatric surgery, but it is affected by several postoperative complications. Endoscopic sleeve gastroplasty (ESG) was created as a less invasive alternative to LSG. However, its efficacy and safety compared with LSG is unclear. Materials and methods Relevant publications were identified in MEDLINE/Cochrane/EMBASE/OVID/ PROSPERO and NIH up to January 2020. Studies were selected that included obese patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…LSG is considered the most commonly performed bariatric surgery worldwide. The safety of the LSG technique, together with high survival rates have been widely demonstrated and LSG has become the surgery procedure of first choice in patients with severe obesity worldwide both in adulthood and pediatric age [ 79 , 87 , 88 , 89 , 90 , 91 , 92 ], and in the adolescent population, LSG appears to have a higher safety profile than other bariatric operations [ 93 ]. The effectiveness of a single procedure in weight loss has been demonstrated in pediatric age [ 88 ].…”
Section: Laparoscopic Sleeve Gastrectomy As Preferred Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…LSG is considered the most commonly performed bariatric surgery worldwide. The safety of the LSG technique, together with high survival rates have been widely demonstrated and LSG has become the surgery procedure of first choice in patients with severe obesity worldwide both in adulthood and pediatric age [ 79 , 87 , 88 , 89 , 90 , 91 , 92 ], and in the adolescent population, LSG appears to have a higher safety profile than other bariatric operations [ 93 ]. The effectiveness of a single procedure in weight loss has been demonstrated in pediatric age [ 88 ].…”
Section: Laparoscopic Sleeve Gastrectomy As Preferred Surgical Approachmentioning
confidence: 99%
“…This technique is also referred to as “greater curvature gastrectomy”, or “vertical gastrectomy” or “pylorus preserving gastric tube”. The vertical resection involves the greater curvature and the fundus and leads to a gastric tuberization [ 88 ] Gastric resection includes approximately 80% of the stomach and the remnant gastric area has a capacity > 100 mL. Gastric reduction does not require a gastrointestinal anastomosis or bypass which makes it easier than RYGB or BPDDS [ 94 , 95 ].…”
Section: Laparoscopic Sleeve Gastrectomy As Preferred Surgical Approachmentioning
confidence: 99%
“…Finally, Marincola et al compared those modalities through a meta-analysis design and confirmed that the surgical approach is superior in weight loss. However, no head-to-head study was included as few cohorts, and no controlled studies comparing those two modalities were available [ 59 ]. Moreover, another meta-analysis demonstrated identical results, but the limitations persist as they are related to the literature itself and not to the methodology of the study [ 60 ].…”
Section: New Data On Well-established Proceduresmentioning
confidence: 99%
“…(Figure 5) This new procedure is called an endoscopic sleeve gastroplasty (ESG) or "endo-sleeve". 12,13…”
Section: Newer Proceduresmentioning
confidence: 99%